Botânica no ensino fundamental: investigação como estratégia pedagógica - Tatsch, Helene Mochetti (2022)
The teaching of Botany has not been highly regarded by students and teachers, because they show a certain rejection to the knowledge about plants, considering it difficult to understand and full of complex terms and processes. Overall, people do not seem to perceive plants apart from their ornamental or feeding role. This lack of interest in Botany can have a direct impact on the preservation and valorization of plant biodiversity, since plants, because they are not known or seen, lose their space in preservation policies. In this work, we seek to propose and analyze practical activities, supported in some aspects of scientific work and aligned to the proposal of Spiral Teaching, for the study of Botany in Elementary School. In order to achieve the proposed objective, the changes proposed by the National Common Curriculum Base (BNCC, initials in portuguese) for the Teaching of Botany were analyzed. Later, we tried to verify, in science textbooks, how the contents on plants were distributed before the BNCC and after it. After this analysis, a didactic sequence was proposed and analyzed for the teaching on plants for the 2° year of elementary school, exploring observation, registration and experimentation. In addition, activities were suggested for the 6° year of elementary school, using experimentation to study the germination process. In order to reduce the lack of perception about plants, we sought to propose and analyze activities that would allow the observation of plants in the environment and in the daily life. To this end, activities were presented using botanical inventory tools and non-formal teaching spaces, which are also thought to be applied to the 6° year of elementary school. With the development of the work, it can be seen that there was a reductionism in the contents of Botany for elementary school at BNCC. However, it was found that practical activities applied in a manner adapted to each level of teaching could contribute to the understanding of plants in a broader way. In addition, the manifestation of botanical blindness was an obstacle to the study of plants and their valorization. Overcoming this scenario can be observed in the development of practical activities with plants and in natural environments, favoring the observation of biodiversity in the context of education. The contributions of this work bring proposals to elementary school teachers who seek to develop the study of plants in a diversified, active and contextual way in order to fill the possible gaps presented by the current curricular proposals.